Comparative study of nasal packs, quilts and splints in septal surgery - Arora, Pankaj; Munjal, Manish; Khurana, Ajit Singh; Munjal, Shubham; Saggar, Tulika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Nasal packing, quilting and splinting are utilized in septal surgery to have a patent airway. The effects on the patient have been studied. Methods: 60 subjects with deviated nasal septum requiring septal surgery were selected from the Rhinology division of otorhinolaryngology services of Dayanand Medical College and Hospital, Ludhiana. Comparison between nasal packing, nasal splints and quilt suturing was carried out in a period of one and a half years. Results: All the 20 patients (100%) of anterior nasal packing had severe local discomfort but no postoperative hematoma. 1 patient (5%) of quilt stitching showed septal swelling and 1 patient (5%) of anterior nasal packing suffered from moderate degree of fever. There was no such episode in any of the patients in whom quilt stitching and splints were used. 6 patients (30%) of anterior nasal packing had crust formation which was not seen in quilt stitching and splint patients. 7 patients (35%) of nasal packing had ulceration of nasal mucosa on removal of pack, while none had in the quilt stitching or nasal splint group. 2 (10%) patients with anterior nasal packing had postoperative synechiae formation. Conclusion: Quilting and splinting are the ideal tamponade post septal intervention As except for mild discomfort they do not experience the unpleasant sequel of accordion nasal packs. Moreover, it makes the procedure a day care surgery.